Analisis Efesiensi Mesin Carnot Dalam Sistem Termodinamika - Cerahman Halawa; Heppy Bulan Seven Halawa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
This study aims to analyze the literature related to the efficiency of the Carnot Engine in thermodynamic systems, focusing on theoretical limitations and factors affecting efficiency in real applications. The Carnot Engine, as an ideal model, provides an illustration of the maximum efficiency limit for the conversion of heat energy into work in a system involving two heat reservoirs at different temperatures. This ideal efficiency, which is determined only by the reservoir temperatures, is difficult to achieve in practice due to irreversibility factors such as friction, imperfect heat transfer, and entropy increase. This literature review presents a deeper understanding of the principles of thermodynamic efficiency, the applications of the Carnot cycle in modern technologies such as power generation and refrigeration systems, and the challenges in approaching ideal efficiency in real engines. The results of this analysis are expected to contribute to improving energy efficiency in various industrial sectors.